2019
DOI: 10.1103/physrevlett.122.036802
|View full text |Cite
|
Sign up to set email alerts
|

Mottness collapse without metallization in the domain wall of the triangular-lattice Mott insulator1TTaS2

Abstract: 1T-TaS 2 is a charge-density-wave (CDW) compound with a Mott-insulating ground state. The metallic state obtained by doping, substitution or pulsed charge injection is characterized by an emergent CDW domain wall network, while single domain walls can be found in the pristine Mott state. Here we study whether and how the single walls become metallic. Tunneling spectroscopy reveals partial suppression of the Mott gap and the presence of in-gap states strongly localized at the domain-wall sites. Using the real-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 65 publications
(78 reference statements)
2
29
1
Order By: Relevance
“…For samples cooled through the C-CDW transition only after cleavage, a surface that retains information about the bulk stacking order may not be expected, since the presence of the surface may set boundary conditions on the CDW formation. In most previous STM reports showing dI/dV data that can be compared against those presented here, the temperature of cleavage was either reported to be room temperature 29,30,35 , or else was unspecified 28,36 . To our knowledge, only in one work was it specified that the cleavage temperature was below the transition temperature into the C-CDW phase 9 , and there a spectrum was shown that appears very similar to the the Type 1 spectrum presented in the current work (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…For samples cooled through the C-CDW transition only after cleavage, a surface that retains information about the bulk stacking order may not be expected, since the presence of the surface may set boundary conditions on the CDW formation. In most previous STM reports showing dI/dV data that can be compared against those presented here, the temperature of cleavage was either reported to be room temperature 29,30,35 , or else was unspecified 28,36 . To our knowledge, only in one work was it specified that the cleavage temperature was below the transition temperature into the C-CDW phase 9 , and there a spectrum was shown that appears very similar to the the Type 1 spectrum presented in the current work (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…S13 for opt-H spectrum) to the Mottness collapse caused by the structural distortion in DWs, 29 however recent studies show that dimerization inside DW precludes metallization. 48 Further spectroscopic studies are thus necessary to build a coherent picture of the transition to the H state from this viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to the emergent corner states at the tri-junctions and corners of the sample boundary, which are akin to those of higher-order topological insulators. [37][38][39] Motivated by references 61,62 where the nature of the insulating domain walls of C-CDW 1T-TaS 2 were discussed, we consider the half-filled wires which can develop a period-2 charge density modulation. When the tri-junction frustrates the charge order and traps solitons, we can show that there is an associated crystal symmetry-protected bound state at the junction (In SI, 41 we provide a few concrete realizations.).…”
Section: (A) the Full Hamiltonian Is Nowmentioning
confidence: 99%